Electrochemical performance and redox stability of solid oxide fuel cells supported on dual-layered anodes of Ni-YSZ cermet and Ni–Fe alloy. (26th January 2022) - Wang, Mengmeng; Li, Naizhi; Wang, Zhongxu; Chen, Chusheng; Zhan, Zhongliang
Abstract: A Ni–Fe alloy layer in combination with a cermet layer composed of Ni and yttria-stabilized zirconia (YSZ) cermet layer was explored as an anode for solid oxide fuel cells (SOFCs). The cell supported on the dual-layered anode with straight pore paths showed a maximum power density of 1070 mW cm −2 at 800 °C, while 737 mW cm −2 for the one supported on the anode with tortuous pore paths. Electrochemical impedance measurement and distribution of relaxation time analysis revealed that the straight pore paths allowed fast gas phase transport thus mitigating the concentration polarization, and improved the accessibility of electrochemical reaction sites hence reducing the activation polarization. The cell supported on the Ni-YSZ/Ni–Fe dual-layered anode remained intact after 8 redox cycles, whereas the cell supported on the Ni-YSZ single layered anode failed after one redox cycle. It is concluded that the Ni-YSZ/Ni–Fe dual-layered composite explored in the present study is suitable for use as the supporting anode for SOFCs. Highlights: Ni-YSZ/Ni–Fe dual-layered anodes were prepared by the phase inversion method. The anode possessed unique straight pore paths allowing facile gas phase transport. The cell with the dual-layered anode showed high electrochemical performance. The cell demonstrated excellent redox stability owing to the Ni–Fe layer.